2023
DOI: 10.1098/rspb.2022.2179
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between the drivers of alpha and beta plant diversity in arable field margins

Abstract: Field margins are major habitats for biodiversity conservation and ecosystem functioning in agricultural landscapes, but biotic homogenization of plant communities threatens their ecological and agronomic functions. Our objective is to determine the drivers of plant diversity in field margins for conservation and restoration purposes. To do so, we assessed the effects of field margin structure and long-term management over 20 years (1995–2015) on the taxonomic and functional α- and β-diversity, and the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Simultaneously, habitat diversity reduced pest colonization in hedgerows adjoining CF fields (same trend for weeds and aphids), providing support for the "resource concentration hypothesis" (Root, 1973). Most likely, semi-natural habitats in diversified landscapes act as barriers to the dispersal of main crop pests (O'Rourke and Petersen, 2017), and may even mitigate agrochemical drifts, thereby limiting the establishment of nitrophilous and herbicide-tolerant plant species (Fried et al, 2018;Boinot and Alignier, 2023).…”
Section: Landscape Variables Related To Semi-natural Habitats Are Key...mentioning
confidence: 83%
See 2 more Smart Citations
“…Simultaneously, habitat diversity reduced pest colonization in hedgerows adjoining CF fields (same trend for weeds and aphids), providing support for the "resource concentration hypothesis" (Root, 1973). Most likely, semi-natural habitats in diversified landscapes act as barriers to the dispersal of main crop pests (O'Rourke and Petersen, 2017), and may even mitigate agrochemical drifts, thereby limiting the establishment of nitrophilous and herbicide-tolerant plant species (Fried et al, 2018;Boinot and Alignier, 2023).…”
Section: Landscape Variables Related To Semi-natural Habitats Are Key...mentioning
confidence: 83%
“…pollination and reduced weed colonization, probably by improving plant-pollinator networks. Indeed, hedgerows with wider canopies provide enhanced habitat and trophic resources in space and time for Hymenoptera pollinators (Donkersley, 2019), and environmental conditions that favour rarer plant species over common weeds (Boinot and Alignier, 2023). Further, carabid conservation increased in hedgerows with wider canopies and higher diversity of woody plant species, and carabid potential predation increased in hedgerows with tall trees.…”
Section: Local Variables Affect Individual Functions Of Hedgerows Mor...mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is important to understand how different alternatives for land management can affect biodiversity in agricultural field boundaries (e.g., hedgerows, shelterbelts, fence lines, roadsides, and wetland margins) as well as natural or seminatural remnants embedded within a matrix of crop fields. Such remnants can provide vital refugia for native flora and fauna in agriculturally‐dominated regions (Clark et al, 2005) and previous research has found that the effects of agricultural practices spill over into adjacent natural/seminatural areas, influencing the diversity of species found there (Boinot & Alignier, 2023; Fried et al, 2018; Metcalfe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%